A strong hydride donating, acid stable and reusable 1, 4-dihydropyridine for selective aldimine and aldehyde reductions. Issue 8 (8th February 2022) - Hirao, Yasukazu; Eto, Hajime; Teraoka, Mitsuru; Kubo, Takashi
Abstract : A new sterically protected 1, 4-dihydropyridine is a stable and regeneratable hydride donor in Brønsted and Lewis acid catalyzed reductions of aldimines and aldehydes. Abstract : A 1, 4-dihydropyridine derivative, lacking carbonyl groups and containing bulky aryl substituents, was synthesized and found to have a high hydride donating ability, acid resistance and reusability. Thermodynamic parameters for electron and hydride transfer in the redox system comprising the 1, 4-dihydropyridine and its corresponding pyridinium ion were determined. In addition, studies showed that the 1, 4-dihydropyridine with steric hindrance can be used to promote efficient, boron trifluoride catalyzed selective reduction reactions of aldimines and aldehydes under mild conditions.